2009
DOI: 10.1097/jcp.0b013e3181934462
|View full text |Cite
|
Sign up to set email alerts
|

HTR2C Gene Polymorphisms and the Metabolic Syndrome in Patients With Schizophrenia

Abstract: In a previous study, we found an association between 5-hydroxytryptamine (serotonin) receptor 2C (HTR2C) polymorphisms and the occurrence of the metabolic syndrome in patients using antipsychotics. In the current study, we set out to replicate our findings in another sample of patients and to explore in a pooled analysis of both samples the influence of the effect of individual antipsychotics. Data for this cross-sectional study came from 2 different samples, the original sample (n = 112) and the replication s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
4
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 19 publications
3
65
4
11
Order By: Relevance
“…In our previous two studies, we used a slightly different set of criteria to diagnose the metabolic syndrome. 8,9 In those two studies, the metabolic syndrome was diagnosed when three or more of the following four metabolic criteria were met: waist circumference 4102 cm (male) or 488 cm (female), triglycerides X1.7 mmol l À1 , HDL cholesterol o1.0 mmol l…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous two studies, we used a slightly different set of criteria to diagnose the metabolic syndrome. 8,9 In those two studies, the metabolic syndrome was diagnosed when three or more of the following four metabolic criteria were met: waist circumference 4102 cm (male) or 488 cm (female), triglycerides X1.7 mmol l À1 , HDL cholesterol o1.0 mmol l…”
Section: Discussionmentioning
confidence: 99%
“…However, in western and northern Europeans, allele G appears to be the major allele, which is confirmed in our earlier research. 8,9 In the analysis we therefore considered the C-allele as the variant allele. For the Asians and Africans in our study, the variant rs1414334 allele would actually be the G-allele.…”
Section: Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 They replicated the finding in a recent report and further demonstrated that, the increased risk for MetS, is particularly strong in carriers of the 5-hydroxytryptamine (serotonin) receptor 2C rs1414334 C allele using clozapine or risperidone. 12 Another study investigated association between methylenetetrahydrofolate reductase genetic variants and MetS in schizophrenic patients receiving AAPs and demonstrated that the methylenetetrahydrofolate reductase 677T allele is associated with a 3.6-fold greater risk for developing AAP-associated MetS and the 677TT genotype may place individuals at greater risk for insulin resistance with greater central adiposity. 13 Two insulin-induced gene (INSIG) isoforms, designated INSIG-1 and INSIG-2, are closely related proteins of the endoplasmic reticulum, encoded by individual gene (INSIG1 and INSIG2, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for the 5-HT2c receptor is an example of a drug targeting receptor with a relatively unknown phenotype. One of the suggested clinical phenotypes of the HTR2C gene is a function in regulation of food intake and weight gain but results are conflicting [18][19][20][21][22][23][24][25]. This pharmacodynamic polymorphism is one example of many others.…”
Section: Resultsmentioning
confidence: 99%